Intensity and timing of the first thinning of Tectona grandis plantations in Costa Rica: results of a thinning trial - Kanninen, M.; Pérez Cordero, L.D.; Montero, M.; Viquez, E. (2004)
During the last two decades, the Costa Rican government has promoted the establishment of Tectona grandis plantations for sawn timber. However, there is a lack of knowledge on optimum spacing and on thinning regimes, in contrast to high expectations of final mean diameter at breast height (DBH) between 35 and 40 cm and stand volumes between 200 and 300 m3 ha-1. The aim of this study was to establish guidelines for plantation management in terms of appropriate intensity and timing of the first thinning (from approximately 4 thinnings recommended in 20–25 year-old rotation management systems). A thinning trial was established in a 4-year old T. grandis plantation that was originally established with initial spacing of 1600 trees ha-1. The experimental design consisted of randomized complete blocks, with eight treatments and three replicates. Each treatment consisted of 80 trees in square blocks of 500 m2. The treatments were of different thinning intensities (from 25% to 60% removal of standing trees, and the unthinned control) applied at two timings (at the ages of 4 and 6 years, and one treatment applied at the ages of 4 and 5 years) and an unthinned control in each replicate. The trees in each treatment were measured annually between age 4 and 8 years. At the age of 8 years, the average DBH for all treatments was 17.5 cm (15.2–20.1 cm) and the total height averaged 18.8 m (17.7–19.5 m). The total volume (Vo) varied from 90 to 200 m3 ha-1, at corresponding BA between 12 and 28 m2 ha-1.The 60% thinning intensity applied at the age of 4 years, and the two consecutive 25% thinnings at the ages of 4 and 5 years gave the highest individual tree growth, while the control was the lowest. The current annual increment (CAI) of DBH was highest in the 40 and 60% thinned treatments. The CAI of DBH and BA decreased rapidly with increasing age in every treatment. The values of CAI of Vo varied between 9 and 39 m3 ha-1 year-1. The high values of CAI of Vo were obtained at BA between 18 and 20 m2 ha-1. At BA of 18 m2 ha-1, Vo was between 120 and 150 m3 ha-1 on a stand conformed by trees with an average DBH between 17 and 20 cm. The recovery of BA and Vo was faster in the treatments carried out at the age of 4 years than at 6 years, when measured 2 years after the thinning. In terms of the remaining stand volume (after thinning), tree size and rate of recovery, the best thinning was at the age of 4 years removing 40–60% of the trees, or consecutively at the ages of 4 and 5 years removing 25% of standing trees in each year. Results of this thinning trial indicate that T. grandis plantations can be managed towards the production of high individual tree growth or towards the production of high stand growth, by means of varying the intensity and timing of the thinning interventions through rotation.